What helps older people persevere with yoga classes? A realist process evaluation of a COVID-19-affected yoga program for fall prevention - Abby Haynes; Heidi Gilchrist; Juliana S. Oliveira; Anne Grunseit; Catherine Sherrington; Stephen Lord; Anne Tiedemann (BMC, 2022)
Abstract Background Falls among older people are a major global health concern. This process evaluation investigates the experience of participants aged 60+ in a yoga program aimed at preventing falls which transitioned from studio-based classes to online classes in response to COVID-19 restrictions. We sought to understand how the Successful AGEing (SAGE) yoga program functioned in both settings and as a hybrid program, and to explain why it worked well for most participants. Methods Realist process evaluation was used to explore the factors that facilitated a successful transition for most participants, and to consider why it did not work for a minority. This approach develops program theories that describe which mechanisms an intervention is (or is not) activating, and how this is mediated by context to generate process outcomes. Data included interviews with participants (n = 21) and yoga instructors (n = 3), self-report feedback forms (n = 46), observation of classes and routine process measures. Results Factors that facilitated a successful transition for most participants included the quality of yoga instruction, the program format and inherent characteristics of yoga. Gains in transitioning online included continuity and greater convenience. Losses included perceived reduction in the effectiveness of yoga instruction. There were greater challenges for people struggling with pain and in disadvantageous home environments. We identified six program theories configured around 16 mechanisms: 1. It's worth the effort and 2. In expert hands (these had the same mechanisms: value expectancy, therapeutic alliance and achievement/mastery), 3. A communal experience (these mechanisms were shared experience, social connection, social comparison and peer checking), 4. Putting yoga within reach (accessibility, convenience, gratitude), 5. Building yoga habits (purposeful structure, momentum, accountability and continuity), and 6. Yoga's special properties (embodiment and mindfulness). Conclusions This study showed that online delivery of a yoga program for people aged 60+ retained much of the value of a face-to-face program for the majority of participants, and increased the value for some. The structured, communal nature of an organised group program delivered by a skilled instructor, together with yoga's intrinsic focus on mindfulness, facilitated continued engagement and perceived health benefits, despite the change in delivery mode.